Effect of Integrated Nutrient Management Practices on Soil Nutrient Availability, Growth and Yield of Sunflower in Kailari, Kailali - Magar, Sangita Gaha; Pandey, Lalit; Joshi, Toyanath; Rajbanshi, Devraj; Rasali, Priyanka; Bohara, Binod (Far Western Review, 2024)
The experiment was conducted from February 2024 to June 2024 in Kailari Rural Municipality, Kailali, Nepal to evaluate the effect of different organic fertilizers and sulfur on soil nutrient availability, growth and yield of sunflower. The experiment was carried out in a randomized complete block design with nine treatments and three replications. The nine treatments comprised of T1- Control, T2- Recommended Dose of Fertilizer(RDF), T3- RDF + Compost manure, T4- RDF + Poultry Manure, T5- RDF + Sulfur, T6- RDF + Compost Manure + Poultry Manure, T7- RDF + Compost Manure + Sulfur, T8- RDF + Poultry Manure + Sulfur, T9- RDF + Compost Manure + Poultry Manure + Sulfur. Results showed that combined application of RDF+CM+PM+Sulfur was found significantly superior on plant height (113.59 cm), stem diameter (22.20mm), f lower diameter (11.60cm), grain per flower (570.11), grain yield (1179.95 kg/ha), biological yield (5799.25 kg/ha). Similarly, the treatments that received organic manure significantly affected soil parameters such as pH, organic matter, available nitrogen, water-holding capacity and porosity. The highest yield was observed in RDF+CM+PM+S (1179.95kg/ha) followed by RDF+PM+S (1121.52 kg/ha) which was 37.77 % and 30.95 % higher than control. This combination also enhanced soil quality by improving various soil parameters, underscoring the benefits of integrated nutrient management for sustainable agriculture. Recommended dose of fertilizers alone had a higher BC ratio (1.79), however recommended dose of fertilizers with compost manure (RDF+CM) was more eco-friendly (1.39 BC ratio).